SB218078 inhibits angiogenesis and epithelial-mesenchymal transition in breast cancer - Wu, Qianxue; Xu, Jiawei; Tang, Xin; Yu, Jin; Li, Benhua; Yang, Jun; Zhang, Xiang (Frontiers in Pharmacology, 2025)
PurposeSmall-molecule inhibitors of vascular endothelial growth factor receptor 2 (VEGFR2) face clinical limitations due to adverse effects. This study aimed to evaluate the novel compound SB218078 as a dual-targeting agent against both tumor angiogenesis and epithelial-mesenchymal transition (EMT) in breast cancer, while exploring its mechanisms of action.MethodsThe anti-angiogenic effects of SB218078 were investigated using in vitro models of endothelial cell migration, invasion, and tube formation, alongside in vivo zebrafish developmental angiogenesis assays. Breast cancer progression was assessed through cellular proliferation, migration, invasion tests, and mouse xenograft models. Mechanistic studies focused on the Chk1/ZEB1 signaling axis, validated through genetic interventions.ResultsSB218078 effectively suppressed angiogenesis by inhibiting endothelial cell functions and disrupting developmental vascular networks in zebrafish. It also impeded breast cancer cell aggressiveness and tumor growth in vivo. Mechanistically, SB218078 selectively targeted ZEB1—an EMT transcription factor—via Chk1 inhibition, with ZEB1 knockdown mimicking its anti-angiogenic effects, while ZEB1 overexpression reversed this activity.ConclusionSB218078 emerges as a promising dual-action therapeutic candidate for breast cancer, simultaneously blocking angiogenesis and EMT through the Chk1-ZEB1 axis. Its specificity for ZEB1, distinct from other EMT regulators, offers a novel strategy to overcome the limitations of traditional VEGFR2 inhibitors, warranting further preclinical development.